Fairness and Reciprocity in the Hawk-Dove Game - Tibor Neugebauer; Anders Poulsen; Arthur J.H.C. Schram (Tinbergen Institute, 2002)
We study fairness and reciprocity in a Hawk-Dove game. This alllows us to testvarious models in one framework. We observe a large extent of selfish and rationalbehavior. Our results are inconsistent with leading models in this field.
Keywords: C72; C92; H41; D44; 330; Hawk-Dove game; reciprocity; fairness.; Verhaltensökonomik; Gerechtigkeit; Spieltheorie; Theorie